Adaptation of domain-specific transformer models with text oversampling for sentiment analysis of social media posts on COVID-19 vaccine - Bansal, Anmol; Choudhry, Arjun; Sharma, Anubhav; Susan, Seba (Computer Science, 2023)
Covid-19 has spread across the world and many different vaccines have been developed to counter its surge. To identify the correct sentiments associated with the vaccines from social media posts, this paper aims to fine-tune pre-trained transformer models on tweets associated with different Covid vaccines, specifically RoBERTa, XLNet and BERT which are recently introduced state-of-the-art bi-directional transformer models, and domain-specific transformer models BERTweet and CT-BERT that are pre-trained on Covid-19 tweets. We further explore the option of data augmentation by text oversampling using LMOTE to improve the accuracies of these models, specifically, for small sample datasets where there is an imbalanced class distribution among the positive, negative and neutral sentiment classes. Our results summarize our findings on the suitability of text oversampling for imbalanced, small sample datasets that are used to fine-tune state-of-the-art pre-trained transformer models, and the utility of having domain-specific transformer models for the classification task.